2013
DOI: 10.1681/asn.2012121148
|View full text |Cite
|
Sign up to set email alerts
|

TNXB Mutations Can Cause Vesicoureteral Reflux

Abstract: Primary vesicoureteral reflux (VUR) is the most common congenital anomaly of the kidney and the urinary tract, and it is a major risk factor for pyelonephritic scarring and CKD in children. Although twin studies support the heritability of VUR, specific genetic causes remain elusive. We performed a sequential genome-wide linkage study and whole-exome sequencing in a family with hereditary VUR. We obtained a significant multipoint parametric logarithm of odds score of 3.3 on chromosome 6p, and whole-exome seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
1
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 42 publications
2
62
1
9
Order By: Relevance
“…5,6 Twentythree autosomal dominant genes have been identified to cause isolated CAKUT, with TNXB, WNT4, and DSTYK being the most recent ones. [7][8][9][10] According to the Mouse Genome Informatics database (http://www.informatics.jax.org), 1768 monogenic mouse models for CAKUT have been described, many of which are recessive and do not have a human disease correlate.…”
mentioning
confidence: 99%
“…5,6 Twentythree autosomal dominant genes have been identified to cause isolated CAKUT, with TNXB, WNT4, and DSTYK being the most recent ones. [7][8][9][10] According to the Mouse Genome Informatics database (http://www.informatics.jax.org), 1768 monogenic mouse models for CAKUT have been described, many of which are recessive and do not have a human disease correlate.…”
mentioning
confidence: 99%
“…We have previously reported that VUR co-segregates with joint hypermobility in a family with TNXB mutation [9]. To provide further evidence that the rare variants identified by us are likely to be pathogenic, we performed joint hypermobility testing on three individuals with rare variants in TNXB .…”
Section: Resultsmentioning
confidence: 98%
“…We have previously reported two of these variants {c.9770C>T (T3257I) and c.3991G>A (G1331R) in families 6606 and 6952 respectively} [9]. All the TNXB variants were annotated using the transcript ENST00000375244 (Supplementary Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, most CAKUT-causing genes reported to date exhibit an autosomal dominant mode of inheritance with variable expressivity and incomplete penetrance (Gbadegesin et al 2013; Hwang et al 2014; McPherson et al 1987; Sanna-Cherchi et al 2013). Nevertheless, mutations in seven recessive CAKUT-causing genes have recently been discovered (Humbert et al 2014; Kohl et al 2014; Saisawat et al 2014).…”
Section: Introductionmentioning
confidence: 99%